The Customary Institution of North Padang Lawas Regency as an Instrument of Bachrum Harahap's Political Power - Harahap, Ikhwanul Maarif (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This article examines the formation, role, and transformation of the Regional Customary Institution (LAD) of North Padang Lawas Regency as a political instrument in local governance dynamics. Historically, the LAD was established to maintain the cultural values, customary structures, and social systems of the Mandailing-Angkola community, which still adheres to the principles ofDalihan NatoluHowever, in the context of local politics, LAD not only carries out cultural functions, but also plays a strategic role in the formation of public opinion, political mobilization, and the legitimacy of candidates in electoral contests. Through a sociological approach and Pierre Bourdieu's capital theory, this article shows that LAD is an arena for the conversion of social, cultural, and symbolic capital utilized by local political elites. Thus, the existence of LAD not only functions as an institution for cultural preservation, but also becomes a significant political instrument in the local democratic process in North Padang Lawas Regency.